2016
DOI: 10.1111/jre.12357
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 inhibits osteoprotegerin expression by human periodontal ligament cells

Abstract: These results suggest that Jagged1 activates Notch signaling in hPDL cells, leading to decreased OPG expression. This may imply an indirect role of Jagged1 on the regulation of osteoclast differentiation via hPDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…It should be noted that NOTCH3 mRNA levels were also upregulated under intermittent compressive stress. However, a previous report demonstrated that the mRNA baseline expression of NOTCH2 was the highest among the four Notch receptor types (Manokawinchoke et al, ). The role of NOTCH3 in this regulatory mechanism could not be excluded.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It should be noted that NOTCH3 mRNA levels were also upregulated under intermittent compressive stress. However, a previous report demonstrated that the mRNA baseline expression of NOTCH2 was the highest among the four Notch receptor types (Manokawinchoke et al, ). The role of NOTCH3 in this regulatory mechanism could not be excluded.…”
Section: Discussionmentioning
confidence: 92%
“…However, there is limited information regarding the function of Notch signaling in hPDLs. The function of Notch signaling may be dependent on cell type, differentiation stage, or microenvironment (Osathanon et al, ,; Zhu et al, ; Ashley et al, ; Manokawinchoke et al, ). As previously mentioned, mechanical stimuli alters the expression of Notch signaling pathway components, leading to changes in cell behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteolysis is principally attributed to bone resorption regulators, i.e. receptor activator of nuclear factor kappa B ligand (RANKL), its cellular receptor RANK and the decoy receptor osteoprotegerin (OPG) . Increased RANKL/OPG ratio induces osteoclasts differentiation and promotes bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the Notch signaling pathway in osteogenesis is conflicting. Previous reports demonstrated that activation of Notch signaling could lead to decreased or increased osteogenic differentiation, osteoporosis, or increased radiodensity (Dishowitz et al, 2014;Engin et al, 2008;Hilton et al, 2008;Manokawinchoke, Sumrejkanchanakij, Subbalekha, Pavasant, & Osathanon, 2016;Tian et al, 2017;Tu et al, 2012). Several scholars found that the effect of Notch signaling was associated with osteoclast maturation stage.…”
Section: Histological Analysismentioning
confidence: 99%